Individual Movements of Physical Training in the Sport of Taekwondo - Kayratdin Uli, Kabulov Abdinayem (European Journal of Life Safety and Stability (2660-9630), 2023)
This article is about the sport of taekwondo. We consider the individual fighting manners of an athlete.